2006
DOI: 10.1007/bf03022506
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of difficult intubation in patients with obstructive sleep apnea syndrome

Abstract: Purpose: It has been speculated that the severity of obstructive sleep apnea syndrome (OSAS) is related to difficult intubation. However, this has not been confirmed in OSAS patients. Thus, we undertook a retrospective study to assess this relationship in patients who had undergone uvulopalatopharyngoplasty (UPPP) surgery for OSAS. Methods:A retrospective case-control study was undertaken following approval from the Institutional Review Board on human studies. The data from 90 patients with a polysomnograph-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 15 publications
0
65
2
4
Order By: Relevance
“…This is a significant finding because the association between sleep apnea and difficult intubation is widely reported. 6 -8 Our data conflict with those published by Hiremath et al, 7 Siyam and Benhamou, 8 and Kim and Lee 6 The former study was a retrospective analysis of patients who had been proven difficult to intubate. 7 Consequently, selection bias is likely, and the study included only 15 patients.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This is a significant finding because the association between sleep apnea and difficult intubation is widely reported. 6 -8 Our data conflict with those published by Hiremath et al, 7 Siyam and Benhamou, 8 and Kim and Lee 6 The former study was a retrospective analysis of patients who had been proven difficult to intubate. 7 Consequently, selection bias is likely, and the study included only 15 patients.…”
Section: Discussioncontrasting
confidence: 63%
“…[1][2][3] A series of studies have demonstrated that Mallampati score and neck circumference (NC) may predict difficult intubation in obese patients undergoing bariatric surgery 2,4 -6 ; the published difficult intubation rate for all MO patients is 10%-16.7%. 2,5,6 In addition, investigators have demonstrated in chart reviews and case-matched studies that the diagnosis of OSA is associated with increased risk of difficult intubation. 6 -8 Because there has been a dramatic increase in the prevalence of OSA associated with the obesity epidemic, these data suggest that clinicians may encounter difficult intubation with increased frequency.…”
mentioning
confidence: 97%
“…The serious and life-threatening complications may occur in patients with OSA and unrecognized OSA during tracheal intubation, extubation, or with postoperative analgesia, since opioids increase the incidence of pharyngeal collapse in the patients with sleep apnea. Difficult airway management, difficult intubation, or prolonged recovery from anesthesia should be considered in an OSA patient and in patients with clinical suspicion of OSA [15,16]. The importance of OSA as a disease entity has been recognized by anesthesiologists recently in developed countries [17].…”
Section: Introductionmentioning
confidence: 99%
“…OSA has been linked to a metabolic syndrome and has been shown to be an independent indicator of increased blood glucose (12,13). In addition, it has been reported that the incidence of congestive heart failure, coronary artery diseases, cerebro- The problems encountered during difficult airway management are known to be the chief cause of life-threatening anaesthetic complications (15). In addition, it is thought that patients with difficult airway management, difficult intubation, or lengthened recovery periods may have OSA (16).…”
Section: Discussionmentioning
confidence: 99%